Acute Implant-related Complications in Pediatric Cervical Spine Fusion. Issue 7 (August 2020) - O'Neill, Nora P.; Hresko, Michael T.; Emans, John B.; Glotzbecker, Michael P.; Verhofste, Bram P.; Karlin, Lawrence I.; Proctor, Mark R.; Hedequist, Daniel J.
Abstract : Background: The use of modern rigid instrumentation in pediatric cervical fusions decreases the risk of implant-related complications, both acute and long term. However, previous studies have indicated that acute implant-related issues still occur in the adult population. Reports of pediatric acute implant complications, occurring within 3 months of surgery, are under-represented in the literature. The purpose of this study is to document the prevalence of acute implant-related complications in a pediatric cervical fusion population. Methods: A retrospective review of instrumented cervical fusions from August 2002 to December 2018 was conducted. Acute implant-related complications were defined as malposition, fracture, or disengagement of cervical instrumentation, including screws, rods, and plates, within 90 days of surgery. Results: A total of 166 cases were included (55% male individuals) with an average age at surgery of 12.5 years (SD, ±5.28). Acute implant-related complications occurred in 5 patients (3%). All 5 patients had a syndromic diagnosis: Loeys-Dietz (n=1), osteopetrosis (n=1), neurofibromatosis (n=1), trisomy 20 (n=1), and achondroplasia (n=1). One case involved asymptomatic screw protrusion, 1 case lateral mass screw pull-out, 2 more had screw-rod disengagement, and the last experienced dislodgement of the anterior plate. The median time until the presentation was 25 days (range, 1 to 79 d). All patients (n=5) required surgical revision. Conclusions: This case series suggests that the overall incidence of acute cervical implant failure is low. However, failure is more likely to occur in patients with underlying syndromes compared with patients with different etiologies. Intraoperative use of 3-dimensional computed tomography imaging is recommended to evaluate the screw position and potentially avoid later surgery.